Relationships between dietary intake and body composition according to gross motor functional ability in preschool-aged children with cerebral palsy - Walker, J.; Bell, K.; Stevenson, R.; Weir, K.; Boyd, Roslyn; Davies, P. (2012)
Background/Aims: We aimed to determine the relationships between energy intake, macronutrient intake and body composition in preschool-aged children with cerebral palsy (CP) according to gross motor functional ability in comparison with typically developing children (TDC). Methods: Seventy-three children with CP (70% male) of all functional abilities and 16 TDC (63% male) aged 2.8 ± 0.9 years participated in this study. Dietary intake was measured via a validated 3-day weighed food record. Body composition was determined via isotope dilution techniques. Results: There was a significant relationship between energy intake and fat-free mass index, which was stronger in TDC compared to children with CP. There were no significant correlations between other dietary intake and body composition variables, despite differences in body composition as ambulatory status declined. Non-ambulant, tube-fed children had significantly lower protein intakes compared to orally fed children. No other differences in macronutrient intake between children with CP and TDC were apparent. Conclusions: Results suggest that relationships between dietary intake and body composition are not evident in this population, but develop over time. Physical activity levels may have a greater impact on body composition at this age. Longitudinal research is required to examine these factors. © 2012 S. Karger AG, Basel.